(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Colletotrichum orbiculare is a phytopathogenic fungus that causes devastating diseases in various crops, leading to significant agricultural losses worldwide. The increasing concerns about the environmental and health risks associated with synthetic fungicides have sparked interest in exploring natural alternatives. Clove oil, derived from the aromatic spice Syzygium aromaticum, has shown promising antifungal properties in previous studies. In this research, we investigated the potential antifungal activity of clove oil against Colletotrichum orbiculare using the Poisoned Food Technique. The research involved preparing different concentrations of clove oil and incorporating them into potato dextrose agar media to evaluate their impact on Colletotrichum orbiculare growth. The experiment was conducted in a controlled environment, and the results were recorded by measuring the radial growth of the fungus. Statistical analyses were performed to assess the significance of the inhibitory effects of clove oil. Our findings revealed that clove oil exhibited significant antifungal activity against Colletotrichum orbiculare. The most potent inhibitory effect was observed at the highest concentration of clove oil tested viz., 40%, 60%, 80% and 100%. These results suggest that clove oil has the potential to be used as a natural and eco-friendly alternative to synthetic fungicides for controlling Colletotrichum orbiculare infections in crops.